Factors Influencing Knee Flexion Range of Movement after Primary Total Knee Arthroplasty : Study of a Consecutive Series over Ten Years - Faustin Atemkeng Tsatedem; Arabo Saidou Mohamadou; Tsiagadigui Jean Gustave; Douryang Maurice; Djam C. Alain; Guifo Marc Leroy; Eone Handy; Farikou Ibrahima; Watcho Pierre (Archives of Current Research International, 2023)
Introduction: Knee flexion after total arthroplasty is not always satisfactory. Our hypothesis: many factors can influence it. Some of these factors have been studied, but with controversial results. Methodology: It was a monocentric prospective and comparative study. All primary total knee replacement were included. For each factor, we compared a group of patients with above mean flexion to those with smaller flexion, using comparison of means, regression analysis and the chi square test. Results: We had 110 arthroplasties from 88 patients. Three preoperative factors affected the outcome: pre-operative knee flexion < 110°, flexum deformity > 5° and a body mass index above 30kg/m2. The respective Pearson coefficient value for these three factors were +0.50, +0.05, and -0.13.The chi square values were respectively 12.019 (p<0.001) and 6.091 (p<0.02) for the first two ones. Mean postoperative flexion values were significantly low for the patients with high body mass index (p<0.03) and for those with knee flexion < 110° (p<0,001). Conclusion: Such studies should be carried out in other settings to prepare later meta-analysis. The effect of early physiotherapy in knee arthritis treatment in preventing knee stiffness at the time of total knee replacement should be evaluated.